Birth cohort, sex and educational disparities in the trajectories of body mass index in Taiwan: a longitudinal study - Tzu-Jung Wong; Tsung Yu; Ly-yun Chang; Xiang Qian Lao (BMC, 2022)
Abstract Background Taiwan has gone through rapid industrialization, urbanization and economic growth in the 20th and early 21st centuries. Therefore, the population has experienced significant changes in the physical and social environment during the life course, which may affect the overall adiposity. Our aim was to examine the age trajectories of height, weight and body mass index (BMI) in the Taiwanese population and to explore the influences of sex, birth cohort and education. Methods The sample comprised 572,358 residents between 20 and 94 years of age in Taiwan who attended at least one health examination during 1996 to 2017 in a cohort study. Repeated measures of body weight and height were collected using an auto-anthropometer. We conducted a series of linear mixed-effects growth curve models to examine the trajectory of height, weight, and BMI across the life course with stratification by sex. Results Age-related trajectories of BMI differed between men and women and stronger cohort effects were observed among men, with younger cohorts having higher BMI. After holding cohort and age variables constant, men with junior high or lower education were shorter, thinner and had higher BMI than men with university or higher education (effect sizes: − 3.138 cm, p < 0.001; − 2.277 kg, p < 0.001; 0.121 kg/m2, p < 0.001, respectively). Women with junior high or lower education were shorter, heavier and had higher BMI than women with university or higher education (effect sizes: − 2.368 cm, p < 0.001; 2.417 kg, p < 0.001; 1.691 kg/m2, p < 0.001, respectively). The educational disparities in BMI were found to be larger among women. Conclusions Our findings suggest that younger generations, especially men, and lower educational level individuals, particularly women, have increasing levels of BMI. The influence of age and cohort effects together with sex and educational disparities on adiposity should be highlighted when designing future interventions and policies regarding overweight and obesity.